Peroxisome proliferator-activated receptor gamma agonist ELB00824 suppresses oxaliplatin-induced pain, neuronal hypersensitivity, and oxidative stress. (1st November 2022) - Zhang, Morgan; Hu, Min; Alles, Sascha R.A.; Montera, Marena A.; Adams, Ian; Santi, Maria D.; Inoue, Kenji; Tu, Nguyen Huu; Westlund, Karin N.; Ye, Yi
Abstract: Chemotherapy-induced neuropathic pain (CINP) is a debilitating and difficult-to-treat side effect of chemotherapeutic drugs. CINP is marked with oxidative stress and neuronal hypersensitivities. The peroxisome proliferator-activated receptor gamma (PPARγ) is a transcription factor that regulates genes involved in oxidative stress and inflammation. We hypothesize that PPARγ agonists are protective against CIPN by reducing oxidative stress and inhibiting neuronal hypersensitivities. To test our hypothesis, acute or chronic CIPN was introduced by short or long-term treatment of oxaliplatin in BALB/c mice. CIPN mice were treated with either a novel blood-brain barrier (BBB) penetrable PPARγ agonist ELB00824, or a BBB non-penetrable PPARγ agonist pioglitazone, or vehicle. Cold allodynia, mechanical allodynia, motor coordination, sedation and addiction were measured with dry ice, von Frey filaments, beam-walking tests, and conditioned place preference, respectively. Oxidative stress was accessed by measuring byproducts of protein oxidation (carbonyl and 3-Nitrotyrosine) and lipid peroxidation [Thiobarbituric acid reactive substances (TBARS)], as wells as gene expression of Cat, Sod2, Ppargc1a . The effects of ELB00824 on nociceptor excitability were measured using whole-cell electrophysiology of isolated dorsal root ganglion neurons. Preemptive ELB00824, but not pioglitazone, reduced oxaliplatin-induced cold and mechanical allodynia and oxidative stress. ELB0824 suppressed oxaliplatin-induced firing in IB4 - neurons. ELB00824 did not cause motor discoordination or sedation/addiction or reduce the antineoplastic activity of oxaliplatin (measured with an MTS-based cell proliferation assay) in a human colon cancer cell line (HCT116) and a human oral cancer cell line (HSC-3). Our results demonstrated that ELB00824 prevents oxaliplatin-induced pain, likely via inhibiting neuronal hypersensitivities and oxidative stress. Highlights: ELB00824 exhibits preventative and acute treatment effects on cold and mechanical pain in mouse models of OIPN. ELB00824 reduces oxidative stress and inhibits neuronal hypersensitivities induced by oxaliplatin. ELB00824 is safe and provides a large therapeutic window.